Establishing a Mining Group of Deposit and an Exploration Grid Pattern for Uranium Ore Intercalated in Sandstone at Pa Lua - Pa Rong Area, Nong Son Basin - Phuong, Nguyen; Dinh Huan, Trinh; Truong Giang, Nguyen; Quyet Tam, Le; Tien Phu, Nguyen; Dinh Than, Nguyen; Le Chau, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2024)
This research shows the results of establishing a mine group and a uranium ore exploration network in Nong Son depression sandstone, Quang Nam province based on the results of exploration of uranium ore bodies in the Pa Lua - Pa Rong area. Some main findings include: i) The uranium content in most industrial ore bodies can be attributed to a lognormal distribution function. The ore bodies (two main ore bodies are referred to as TQ1 and TQ2) have an average uranium concentration from 0,032% to 0,054% U3O8 with high variations (with the amount of variation in content (Vc) greater than 100%). The average thickness of the ore bodies is from 2,30 meters to 2,35 meters. The thickness variation coefficient (Vm) varies from 89,4% to 100,3%, indicating the unstable to very unstable type of ore body; and ii) Uranium mines in sandstones of the Pa Lua - Pa Rong type, Nong Son basin mainly belong to exploration mine group III. The most reasonable exploration approach is to use a parallel and fan-shaped network. To calculate the reserves, the distance between drilling routes is set at 50 to 60 meters. To determine the road and pavement, wet set the drilling routes to be 25 to 30 meters apart from each other. This exploration network can be applied to other sandstone mines in the Nong Son basin with similar characteristics to the Pa Lua - Pa Rong mine.